From Small Places - Wilson-Keenan, Jo Anne. author. aut Link
XXVIII, 230 p.
Keywords: From Small Places: Toward the Realization of Literacy as a Human Right brings together history, theory, research, and practices that can lead to the realization of this right, both in itself, and as a means of achieving other rights. The premise of this book is that this right begins early in life within small places across the world. This idea originates from the words of Eleanor Roosevelt, Chair of the Commission that drafted the Universal Declaration of Human Rights (UDHR): Where, after all, do universal human rights begin? In small places, close to home—so close and so small that they cannot be seen on any map of the world… Unless these rights have meaning there, they have little meaning anywhere. Herein, literacy is viewed as a life-long social process. Literacy includes reading, writing, and new literacies that are evolving along with new technologies. The book includes an examination of the evolution of literacy as a human right from 1948, the time of the writing of the UDHR, to the present. Barriers to the realization of literacy as a human right, including the pedagogy of poverty and pathologizing the language of poor children, are explored. The book also describes theory, research and practices that can serve to dismantle these barriers. It includes research about brain development, language and literacy development from birth to the age of six, and examples of practices and community initiatives that honor, support, and build upon children’s language and literacy.